Black pitch, carved histories: Radiocarbon dating, wood species identification and strontium isotope analysis of prehistoric wood carvings from Trinidad's Pitch Lake. (December 2017) - Ostapkowicz, Joanna; Brock, Fiona; Wiedenhoeft, Alex C.; Snoeck, Christophe; Pouncett, John; Baksh-Comeau, Yasmin; Schulting, Rick; Claeys, Philippe; Mattielli, Nadine; Richards, Mike; Boomert, Arie
Graphical abstract: Abstract: We report on the results of a multi-disciplinary project (including wood identification, radiocarbon dating and strontium isotope analysis) focused on a collection of pre-Columbian wooden carvings and human remains from Pitch Lake, Trinidad. While the lake's unusual conditions are conducive to the survival of organic artefacts, they also present particular challenges for analysis. There is a loss of any contextual association beyond that of the lake, and specific methodologies are required to deal with pitch contamination. A surprising taxonomic range of woods was employed for the various utilitarian and ceremonial items recovered. The 14C results range from ca. 3200 BCE to ca. 700 CE, and include the earliest known wooden carvings in the entire Caribbean. The strontium isotope results - interpreted with the aid of an isoscape developed for the project, based on extensive samples of modern trees across Trinidad and Tobago - indicate that most carvings are consistent with the site's immediate environs; however, a 'weaving tool' came from a more radiogenic region that is unlikely to be found on Trinidad, suggesting links with the South American mainland. Highlights: 14 C dates wood identifications and 87 Sr/ 86 Sr results from 10 wooden artefacts recovered from Pitch Lake, Trinidad, are reported. 14 C results range from ca. 3000 BCE to 690 CE, and include the earliest directly dated wooden artefacts from the Caribbean. carving materials include Andira sp., Brosimum cf. guianensis, Carapa sp. and Platymiscium sp. 87 Sr/ 86 Sr results for nine carvings are consistent with a local origin, while the tenth, a weaving tool, likely derives from a more radiogenic region, the nearest of which is the South American mainland. also recovered from the Lake is a partial human cranium directly dated to the Archaic Age.